Epidemiological Studies of Polyparasitism in Two Different Communities in Benue State, Nigeria - Edward A. Omudu,; Emmanuel Onah,; Matthew Emberga-Biem, (Journal of King Abdulaziz University: Medical Sciences, 2023)
To advance knowledge on polyparasitism in Nigeria. This study examined parasitic infections and co-infections in two contrasting communities in Benue State, Nigeria. Urine specimens were evaluated for Schistosoma haematobium using the filtration technique, stool specimens were examined for intestinal parasites using the concentration technique, and blood specimens were examined using the thick and thin film technique for Plasmodium species. Results show high prevalence of infections in both populations, with 26.9% of participants carrying a single parasitic infection. Co-infection with two parasites was recorded in 9.1% while multiple infections with three parasites were recorded in 0.7% of participants. The prevalence rates in the two communities was significantly different (df = 1, p < 0.05). There were differences in infection rates between male and female participants. Of the 316 male examined, 26.6% and 8.9% had single and double infection rates, while the 375 female had 27.2% and 9.3% single and double infection rates. These gender differences are not statistically significant (p > 0.05). Six parasites were identified, with Schistosoma haematobium, Plasmodium falciparum and Ascaris lumbricoides accounting for the most frequent combination of parasite species. The synergistic impact of multiple parasitisms on the individual and community are discussed and the need to explore the consequences of these relationships stressed